Penyelesaian Sengketa Skincare - Fiska Silvia Raden Roro; Bambang Sugeng Ariadi Subagyono; Zahry Vandawati Chumada; Trisadini Prasastinah Usanti (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
A community service program (PKM) entitled "Skincare Product Dispute Resolution" was successfully implemented in Ngadi Village, Mojo District, Kediri Regency, involving village cadres, youth organizations, and community members, particularly housewives as skincare consumers. This PKM aims to provide solutions to skincare product disputes through five stages: outreach, training, technology implementation, mentoring, and sustainability evaluation. The outreach program began with a presentation on halal skincare products and consumer protection against misleading promotional practices, delivered by speakers from the Sharia Research Group (SReG) and the Non-Governmental Consumer Protection Organization. This program also includes in-kind and in-cash contributions, including training to improve customer service quality, ensure raw material quality standards and production processes comply with international standards, and ensure product information transparency. In addition, a loyalty program and transportation cost incentives were provided to affected consumers. PKM partners played an active role in providing information and inviting the community to participate in this activity. The implementation of this activity is expected to strengthen consumer trust and ensure protection of consumer rights related to skincare products.